The impact of IAS 39 on the risk-relevance of earnings volatility: Evidence from foreign banks cross-listed in the USA - Duh, Rong-Ruey (2014)
We examine the impact of adopting International Accounting Standard 39 – Financial Instruments: Recognition and Measurement (IAS 39) by non-US commercial banks cross-listed in the US on earnings volatility and its risk relevance. As IAS 39 requires the recognition of unrealized fair-value gains and losses for a larger set of financial and derivative- financial instruments, and the impairment charges for loans and receivables, we expect and find that IAS 39 adoption increased earnings volatility in IFRS-adopting firms from 2005 onwards. Furthermore, both hedge accounting and the fair value option under IAS 39 are designed to reduce mixed-measurement volatility and to improve the sensitivity of firm risk measures to earnings volatility. We also find that the relationship between credit ratings (proxy for risk) and earnings volatility increases for IFRS-adopting firms after 2005. The evidence is consistent with the argument that IAS 39 increases the credit relevance of earnings volatility.